Male medical sciences students' perceptions of the positive aspects of dormitory life related to the quality of academic life: A phenomenological study - Mohammad Hossein Akhondi; Mohsen Shakeri; Kazem Barzegar Bafrooei; Hossain Hassani (Journal of Medical Education Development)
Background & Objective: The purpose of this study was to investigate the perceptions of male medical sciences students at Yazd University regarding the positive aspects of dormitory life and its impact on academic quality during the 2022-2023 academic year. Material & Methods: Using a qualitative and phenomenological method, 11 Yazd University dormitory students were chosen for the study using a criterion-based purposive sample technique. Semi-structured in-depth interviews were used to gather data, and they were conducted until data saturation was achieved. The Smith method was used for data analysis, and triangulation was used to ensure the accuracy of the results. Results: Three primary topics and seventeen supporting themes on students' experiences living in dorms and how it affected the quality of their education were found in the study. These themes, which were acknowledged as beneficial aspects of living in a dorm, included: Having a supportive atmosphere; Developing personal and professional capacities; and Ease of education and life. Conclusion: Research indicates that policymakers and planners can improve the quality of education and create more capable graduates for society by capitalizing on the advantages of living in dorms for medical students.